2014
DOI: 10.1097/01.prs.0000455550.52953.ed
|View full text |Cite
|
Sign up to set email alerts
|

Minced Nerve Tissue in Vein Grafts Used as Conduits in Rat Tibial Nerves

Abstract: PLASTIC SURGERY 2014, Abstract Supplement 164 Figure 1.CONCLUSIONS: Women with larger BMI experience significantly higher rates of mastectomy alone without reconstruction despite having higher satisfaction with reconstruction and similar satisfaction with breast conservation surgery. This supports the notion that all patients being considered for mastectomy should be referred to a plastic surgeon for evaluation and plastic surgeons should highly consider use of abdominal fl ap reconstruction in this population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Although some studies have shown that the application of an EC has a positive effect on nerve regeneration as well as prevention of neuroma formation and muscle denervation atrophy, to the best of our knowledge, this is the first study reporting the use of the human epineurium as a biomaterial for the creation of the EC and application of the EC in the regeneration of nerve gaps. 15 28…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown that the application of an EC has a positive effect on nerve regeneration as well as prevention of neuroma formation and muscle denervation atrophy, to the best of our knowledge, this is the first study reporting the use of the human epineurium as a biomaterial for the creation of the EC and application of the EC in the regeneration of nerve gaps. 15 28…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of published papers determined that for nerve gaps up to 4 cm in length, vein conduits did not induce any significant improvement in sensory recovery outcome compared to conduits of other materials [170]. However, the axon regeneration-promoting efficacy of vein conduits is enhanced when they are filled with PRP [171][172][173], muscle [174], pre-degenerated muscle [175,176], muscle seeded with neural-transdifferentiated human mesenchymal stem cells [177], and minced peripheral nerves [178]. One study in sheep showed that using the median epineural sheath as a conduit can restore median nerve function across 6-cm-long nerve gaps [179].…”
Section: Conduit Compositionmentioning
confidence: 99%
“…In 1986, Smahel and Jentsch used a rat femoral nerve defect to show that nerve regeneration through an autogenous venous conduit was achieved by embedding nerve segments within the venous conduit (Smahel & Jentsch, 1986). Using a similar experimental model, Sahin and colleagues demonstrated that nerve regeneration can be induced by incorporating manually shredded nerve tissues within the venous conduit (Sahin et al, 2014). In 2008, Hung and Dellon applied this approach in a clinical setting, harvesting a 3‐mm nerve segment from the proximal nerve stump of a 5‐cm median nerve defect and placing it within the biodegradable nerve conduit to reconstruct the median nerve, with improved sensory and motor function noted postoperatively (Hung & Dellon, 2008).…”
Section: Introductionmentioning
confidence: 99%